Resilience, Acculturative Stress, and Family Norms against Disclosure of Mental Health Problems among Foreign-Born Filipino American Women - Andrew Thomas Reyes; Reimund Serafica; Chad L. Cross; Rose E. Constantino; Rogelio A. Arenas (JMIR Publications, 2018)
The present study explores the relationships between resilience, acculturative stress, and family norms against disclosure of mental health problems among foreign-born Filipino American women. The sample consisted of 159 foreign-born Filipino American women aged 18 years and above and residing in Las Vegas, Nevada, United States. Participants completed paper-and-pencil questionnaires. Results indicated high levels of resilience and moderate levels of acculturative stress. Findings also showed a significant negative correlation between resilience and acculturative stress, and a significant predictive effect of resilience on acculturative stress. We also found a significant negative relationship between resilience and family norms against disclosure of mental health problems but no significant mediating effect of resilience on the relationship between acculturative stress and family norms. This lack of significant findings related to the mediating effect of resilience on the relationship between acculturative stress and family norms against disclosure of mental illness may be due to the absence of theoretical models and research regarding the role of resilience in the context of acculturation among Filipino American women. Our findings imply the need to further explore underlying mechanisms that explain the relationships between resilience, acculturative stress, and family norms. The findings of the study also confirm the need to develop interventions and resources that ameliorate acculturative stress and promote an increase of the disclosure and reporting of mental health problems among Filipino American women.